Raising the Quality of Secondary Education in East Asia - Nabeshima, Kaoru (World Bank, Washington, DC, 2014)
The author seeks to broaden our understanding of the determinants of student achievement among East Asian economies using the TIMSS-R data set and, in the process, to remedy some of the ambiguities in the literature to date. These ambiguities are frequently due to the sparseness of detailed data on students, teachers, and schools. The TIMSS-R data set offers detailed information on these variables, which is not typically available from other sources, allowing the author to isolate the impact of various factors affecting student achievement, while controlling for specific characteristics of the students, teachers, and schools surveyed. The results indicate that the most consistent factors affecting student performance are characteristics associated with students (innate abilities and home resources). Moreover, the author does not find any consistent relationship between the performance of students and school resources or teacher autonomy, both of which are often advocated in the discussion of education reform.